Corporate Governance The McGraw-Hill Executive MBA Series - Colley. John L. (New York Mcgraw-Hill, 2003)
Accounting "irregularities," lavish payouts to underperforming executives, and other shell-game tactics have led to legitimate questions on the roles and powers of today's director. Corporate Governance examines this volatile situation from its legal, ethical, and operational perspectives, and provides useful insights for board members, managers, investors, and others on how directors can help--or hurt--a corporation. Corporate decision makers, active or aspiring board members, and anyone seeking a more thorough understanding of today's governance process can look to Corporate Governance for frontline details on: Legal and ethical obligations of directors The board's role in strategy formulation Early warning signs of a board in trouble A high-quality, diverse board of directors is critical to a corporation's success. Let Corporate Governance provide you with a clear-eyed view of the governance process, and arm you with proven guidelines for improving the performance of boards of directors as well as the individuals who compose those boards
Includes Index
Keywords: Board Organisation, Board Selection Capital Structures Board Management Corporate Governance